Design and 3D printing of ceramic maxillofacial prosthesis with gradient pores based on Voronoi-Tessellation principle. (December 2022) - Wu, Haidong; Chao, Long; Zhang, Qiuwei; Yi, Yingjie; Jiao, Chen; Ye, Yun; Shen, Lida; Zhao, Jianfeng; Wu, Guofeng; Wang, Changjiang
Abstract: Maxillofacial repair is a challenge in oral and maxillofacial surgery. The manufacture of personalized maxillofacial prosthesis is particularly important. In this article, the specific method of fabricating Al2 O3 ceramic prosthesis for mandibular reconstruction is reported based on digital light processing (DLP) additive manufacturing to address the maxillofacial defect and its mechanical properties were evaluated. Based on Voronoi-Tessellation principle a maxillofacial prosthesis structure was designed to ensure uniform stress distribution. The stress distribution caused by the transmission of occlusal force from implant to maxillofacial prosthesis was investigated. The results of finite element analysis simulation showed that the maxillofacial prosthesis designed according to Voronoi-Tessellation principle effectively reduced the stress generated by dental implants and the prosthesis itself during tooth engagement. The corresponding repair structure shows more uniform stress distribution. The maximum stress of the structure itself was reduced by about 46% compared with other structures. According to the simulated stress distribution, the method of mesh density division was introduced. The maxillofacial prosthesis with gradient pore structure was designed by increasing density in high stress area and decreasing density in low stress area. The fabrication of ceramic maxillofacial prosthesis was verified by DLP. Graphical Abstract: ga1 Highlights: Maxillofacial prosthesis with irregular hole arrangement of bionic trabecular bone was designed based on Voronoi-Tessellation principle. Digital light processing (DLP) method was adopted to satisfy the forming requirements of complex and porous ceramic structures. The designed structure had more uniform stress distribution and the maximum stress was reduced by about 46 %. The lattice density division method was introduced to optimize the maxillofacial prosthesis with gradient pores structure.